Tingkat Adopsi Inovasi Pengelolaan Tanaman Terpadu (PTT) Padi Sawah di Kecamatan Leuwiliang, Kabupaten Bogor - Ismilaili Ismilaili; Ninuk Purnaningsih; Pang S Asngari (Jurnal Penyuluhan, 2015)
Integrated crop management (ICM) can increase productivity, economic benefit rice farming through the efficient use of inputs, and conserve land resources for sustainable production systems. The purpose of this study is to analyze the degree of adoption, perception of ICM, and factors that influence the adoption of innovation ICM of paddy in Leuwiliang District. The research location was in Barengkok village and Leuwimekar village, Leuwiliang Sub-district. Research was implemented from May until July 2014. Respondents in this study were 80 farmers. The respondent covered 40 farmers from the Barengkok village and 40 farmers from Leuwimekar village. The data was collected by using a questionnaire and in-depth interviews. Multiple regression analysis test was used to analyze the data. The research results showed (1) The adoption level of integrated crop management (ICM) of paddy in the Leuwiliang Sub district was in high category, and (2) The factors of age, experience, land area, the availability of technology information, knowledge and perceptions of farmers were significantly affected the adoption level of ICM paddy.Keywords: adoptiom, innovation, paddy field in Leuwiliang, integrated crop management